O desvelamento do sujeito e da morte no discurso dos epitáfios - Loureiro, Raquel Vaccari de Lima (2011)
This dissertation is about the construction of the scenography and the unveiling of the dicoursive ethos in the grave inscriptions’ discourse, the so-called epitaphs, according to the perspective indicated by Dominique Maingueneau (1997, 2001, 2008a, 2008b, 2008c, 2010), in the French line of Discourse Analysis. We found in Maingueneau the concept of discoursive ethos to characterize the image of the enunciating subject, presented or construed by that enunciating subject in the selected discourse. About the scenography, also analyzed through Maingueaneau’s principles, it will subsidize us to unveil, in the epitaphs’ discourses, how society sees death. In order to construe the corpus, we selected grave epitaphs from the cemetery Santo Antônio, in Vitória city, ES, Brazil. In order to list the enunciating characteristics of the epitaph discourse’s subject, we analyzed the components of the discourse gender epitaph, the conception of death, as well as the modality of that discourse, in order to confirm the hypothesis of existing in that discourse a strong religious influence, leading the individuals to recur to the epitaphs as one of the possible forms to construct a “positive” image of their deceased, besides honoring them. Therefore, society uses epitaph discourses as a mechanism to eternize the memory of their deceased. The theoretical option is, therefore, the Discourse Analysis according to Maingueneau, using the categories interdiscourse, enunciation scenes, as well as the components of global semantics as proper enough to reach our goals. The importance of this inquiry is to show that the discourse is the place where the enunciating subject’s image is generated; therefore, it is justified, in this dissertation, to seek to unveil the discoursive ethos of that subject in the epitaph discourse and, at the same time, to perpetuate socio-historically its memory.